Interactions between terpinen-4-ol and nystatin on biofilm of Candida albicans and Candida tropicalis - Tonon, Caroline Coradi [UNESP]; Francisconi, Renata Serignoli [UNESP]; Bordini, Ester Alves Ferreira [UNESP]; Huacho, Patrícia Milagros Maquera [UNESP]; Sardi, Janaína de Cássia Orlandi; Spolidorio, Denise Madalena Palomari [UNESP] (FapUNIFESP (SciELO), 2018)
The aim of this study was to evaluate the antifungal activity of Terpinen-4-ol associated with nystatin, on single and mixed species biofilms formed by Candida albicans and Candida tropicalis, as well as the effect of terpinen-4-ol on adhesion in oral cells and the enzymatic activity. The minimum inhibitory concentrations and minimum fungicide concentrations of terpinen-4-ol and nystatin on Candida albicans and Candida tropicalis were determined using the microdilution broth method, along with their synergistic activity (“checkerboard” method). Single and mixed species biofilms were prepared using the static microtiter plate model and quantified by colony forming units (CFU/mL). The effect of Terpinen-4-ol in adhesion of Candida albicans and Candida tropicalis in coculture with oral keratinocytes (NOK Si) was evaluated, as well as the enzymatic activity by measuring the size of the precipitation zone, after the growth agar to phospholipase, protease and hemolysin. Terpinen-4-ol (4.53 mg mL-1) and nystatin (0.008 mg mL-1) were able to inhibit biofilms growth, and a synergistic antifungal effect was showed with the drug association, reducing the inhibitory concentration of nystatin up to 8 times in single biofilm of Candida albicans, and 2 times in mixed species biofilm. A small decrease in the adhesion of Candida tropicalis in NOK Si cells was showed after treatment with terpinen-4-ol, and nystatin had a greater effect for both species. For enzymatic activity, the drugs showed no action. The effect potentiated by the combination of terpinen-4-ol and nystatin and the reduction of adhesion provide evidence of its potential as an anti-fungal agent.
Keywords: Candida albicans; Candida tropicalis; Nystatin; Synergism; Terpinen-4-ol